Local hemostatic measures in anticoagulated patients undergoing oral surgery: a systematized literature review - Costa,Fábio Wildson Gurgel (2013)
PURPOSE: To conduct a systematized review of the literature about the main local hemostatic measures to control postoperative bleeding in anticoagulated patients. METHODS: A systematized review of literature was performed in the electronic database Medline (PubMed) without restriction of the publication date. The eligibility criteria were studies involving maintenance of the anticoagulant therapy, prospective studies, retrospective studies, randomized clinical trials, controlled clinical studies, comparative studies, multicentric studies or case-control studies. Studies discontinuing anticoagulant therapy, case reports, literature reviews, in vitro studies, animal experiments and articles written in language not compatible with the search strategy adopted in this work were excluded. RESULTS: Twenty-four articles that met the adopted eligibility criteria were selected, enrolling 3891 subjects under anticoagulant therapy. A total of 171 cases of hemorrhage was observed. Tranexamic acid was the main local hemostatic measure used to controlling of postoperative bleeding. CONCLUSION: The local hemostatic measures proved to be effective according to previously published studies. Nevertheless, further clinical studies should be conducted to confirm this effectiveness.